INTERACTION OF COLLINEAR CRACKS IN SPHERICAL SHELL WITH FLEXIBLE COATING - Shatskyi, I. P.; Makoviichuk, M. V.; Shcherbii, A. B. (Computer Science and Applied Mathematics, 2017)
Elastic and limit equilibrium of tensioned shallow spherical shell weakened by two through the thickness meridional cracks and enhanced by coating on one of the face surfaces is studied in the twodimensional formulation. The cracks in the shell with a flexible coating are simulated by cuts with eccentrically hingedly connected edges. The boundary problem for equations of classical shell theory with interrelated conditions of tension and bending along the cutting line is formulated within the framework of such model. Singular integral equation for the unknown jump of normal displacement on the cracks edges has been elaborated. Based on numerical solutions of integral equation dependences of forces and moments intensity factors in the vicinity of the defects tips and distribution of forces in the hinge joints on the parameter of shell curvature and mutual distance between cracks are investigated. To estimate the influence of flexible coating on the limit state of the thin-walled elements of constructions with defects the combined fracture criterion which takes into account two mechanisms: propagation of the crack along the shell body and disintegration of the coating with limited strength, were proposed. The first mechanism is implemented in the shell of small curvature (with short cracks), and the second one – in the shell of big curvature (with long cracks). It was discovered that enhancing of external surface of tensioned spherical shell by coating is more efficient than enhancing of internal one. In addition, the limiting load depends from distance between cuts nonmonotonically in case of strengthening of external face of shell.